2013
DOI: 10.1111/een.12079
|View full text |Cite
|
Sign up to set email alerts
|

The roles of top and intermediate predators in herbivore suppression: contrasting results from the field and laboratory

Abstract: Intraguild predators can have unpredictable effects in food webs: they can either disrupt or enhance herbivore suppression, depending on their direct effects on herbivores. Furthermore, intraguild predation is not always unidirectional, with top predators eating more effective intermediate predators. In a vineyard field experiment and a series of laboratory experiments, the effect of intraguild interactions between a likely top predator (the spider Cheiracanthium mildei) and an intermediate predator (the spide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…Holes on either side of the cages allowed access to vines, and could be opened and resealed with metal clips. Previous studies found no cage effects on spiders or leafhoppers when using this cage design (Hogg & Daane, , ).…”
Section: Methodsmentioning
confidence: 65%
See 4 more Smart Citations
“…Holes on either side of the cages allowed access to vines, and could be opened and resealed with metal clips. Previous studies found no cage effects on spiders or leafhoppers when using this cage design (Hogg & Daane, , ).…”
Section: Methodsmentioning
confidence: 65%
“…The voracity of C. mildei may explain this discrepancy. Cheiracanthium mildei appears to be a particularly voracious species (Hogg & Daane, , ). Hunger can increase the frequency of cannibalism in spiders (Samu et al , ; Petersen et al , ), and C. mildei may have a higher satiation threshold than many other spider species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations